Learning in social media on Education Non formal Department : Literature Review - Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2022)
The objective of this research is to examine the philosophical and theoretical underpinnings of non-formal education (NFE) and to explain its current status as a significant educational force in the postmodern era. Instead of being "extracurricular activities" or "supplementary education," NFE has grown into a global enterprise in education. It hasn't, however, been researched as a stand-alone teaching strategy. Targeting individuals of all ages and reading abilities, NFE questions established notions of education. It has an impact on individuals' lives and conduct as well as society at large. It has also influenced formal education, which has incorporated many of its pedagogical techniques and theoretical presumptions.